Change in the Presence of Residual Fit: Can Competing Frames Coexist? - Gilbert, Clark G. (Organization Science, 2006)
Opportunities associated with discontinuous change typically do not trigger organizational response until the opportunity is perceived as a threat. However, threat perception can then trigger a response that accentuates organizational rigidity. This cognitive paradox is explored using a multilevel, longitudinal case study of a newspaper organization’s response to digital publishing. The results suggest that the competing frames of threat and opportunity can coexist within the firm when it creates organizationally differentiated subunits. Such a structure minimizes the need to integrate competing frames at the subunit level, enabling different behaviors to be enacted simultaneously across different units of the firm. This differentiated organizational form places an increased burden on senior teams that have to manage the inconsistencies across subunits. Insight into the structure of competing frames has broader implications for the structure of dynamic capabilities.